From brain to spinal cord: neuromodulation by direct current stimulation and its promising effects as a treatment option for restless legs syndrome - Dirks, Christina A. H.; Bachmann, Cornelius G. (Frontiers in Neurology, 2024)
Neuromodulation is a fast-growing field of mostly non-invasive therapies, which includes spinal cord stimulation (SCS), transcranial direct current stimulation (tDCS), vagal nerve stimulation (VNS), peripheral nerve stimulation, transcranial magnetic stimulation (TMS) and transcutaneous spinal direct current stimulation (tsDCS). This narrative review offers an overview of the therapy options, especially of tDCS and tsDCS for chronic pain and spinal cord injury. Finally, we discuss the potential of tsDCS in Restless Legs Syndrome as a promising non-invasive, alternative therapy to medication therapy.